2004
DOI: 10.1289/ehp.7046
|View full text |Cite
|
Sign up to set email alerts
|

Hair Mercury Levels in U.S. Children and Women of Childbearing Age: Reference Range Data from NHANES 1999–2000

Abstract: Exposure to methyl mercury, a risk factor for neurodevelopmental toxicity, was assessed in U.S. Hair mercury levels were associated with age and fish consumption frequency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
182
6
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 313 publications
(209 citation statements)
references
References 34 publications
(39 reference statements)
19
182
6
2
Order By: Relevance
“…Consistent with other studies in children (Batista et al 1996;Ip et al 2004;McDowell et al 2004;Pesch et al 2002) and adults (Airey 1983;Hightower and Moore 2003;McDowell et al 2004;Morrissette et al 2004), fish consumption was strongly associated with H-Hg such that children who ate fish weekly or more often were over eight times as likely to have high (≥1 μg/g) levels of H-Hg than children who ate fish less than twice a month.…”
Section: Discussion Hair Hgsupporting
confidence: 88%
See 3 more Smart Citations
“…Consistent with other studies in children (Batista et al 1996;Ip et al 2004;McDowell et al 2004;Pesch et al 2002) and adults (Airey 1983;Hightower and Moore 2003;McDowell et al 2004;Morrissette et al 2004), fish consumption was strongly associated with H-Hg such that children who ate fish weekly or more often were over eight times as likely to have high (≥1 μg/g) levels of H-Hg than children who ate fish less than twice a month.…”
Section: Discussion Hair Hgsupporting
confidence: 88%
“…The mean values for H-Hg over the five years of the NECAT study (0.3-0.4 μg/g hair) were higher than the mean of 0.22 μg/g seen in younger children (ages 1-5) in the 1999-2000 NHANES (McDowell et al 2004). This is likely due to the higher levels of fish consumption in the NECAT children, relative to the national sample of NHANES.…”
Section: Discussion Hair Hgmentioning
confidence: 61%
See 2 more Smart Citations
“…In mothers, the 90th percentile (P90) was half that of the population reference values of the Flemish 2007-2008 biomonitoring study (Milieu Gezondheid 2010), and the US NHANES 1999-2000 study (McDowell et al 2004), as shown in Table 3. Although these studies showed an increase in mercury in hair with age, the mean level of mercury measured in the mothers' hair was lower than the level measured in the children's hair; other studies have also reported no association with mercury levels in hair and age (Cordier et al 1998;Li et al 2008;Wranova et al 2009).…”
Section: Discussionmentioning
confidence: 98%